2017
DOI: 10.3389/fmicb.2017.02485
|View full text |Cite
|
Sign up to set email alerts
|

Probing Genomic Aspects of the Multi-Host Pathogen Clostridium perfringens Reveals Significant Pangenome Diversity, and a Diverse Array of Virulence Factors

Abstract: Clostridium perfringens is an important cause of animal and human infections, however information about the genetic makeup of this pathogenic bacterium is currently limited. In this study, we sought to understand and characterise the genomic variation, pangenomic diversity, and key virulence traits of 56 C. perfringens strains which included 51 public, and 5 newly sequenced and annotated genomes using Whole Genome Sequencing. Our investigation revealed that C. perfringens has an “open” pangenome comprising 116… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
78
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 91 publications
11
78
0
1
Order By: Relevance
“…2B). This analysis suggests a potential widespread reservoir of this C. perfringens lineage given they are genetically highly-similar, and previous studies have indicated this species has a highly divergent genome [20-22].…”
Section: Resultsmentioning
confidence: 52%
“…2B). This analysis suggests a potential widespread reservoir of this C. perfringens lineage given they are genetically highly-similar, and previous studies have indicated this species has a highly divergent genome [20-22].…”
Section: Resultsmentioning
confidence: 52%
“…All C. perfringens can secrete alpha‐toxin (CPA). As the most important exotoxin of C. perfringens , alpha‐toxin has been regarded as the most important research object by researchers (Chen et al, ; Hosomi et al, ; Kiu, Caim, Alexander, Pachori, & Hall, ). CPA is a multifunctional zinc metalloenzyme with phospholipase C activity at the amino‐terminus.…”
Section: Discussionmentioning
confidence: 99%
“…Genes encoding accessory virulence factors, such as beta-2 toxin, were commonly detected (46.7%; 50/109), and genes encoding phage proteins were also frequently identified, with additional analysis indicating their contribution to increased virulence determinants within the genomes of gastroenteritis-associated C. perfringens . Overall this large-scale genomic study of gastroenteritis-associated C. perfringens suggested that 3 major sub-types underlie these outbreaks: strains carrying (1) pCPF5603 plasmid, (2) pCPF4969 plasmid, and (3) strains carrying cpe on transposable element Tn 5565 (usually integrated into chromosome). Our findings indicate that further studies will be required to fully probe this enteric pathogen, particularly in relation to developing intervention and prevention strategies to reduce food poisoning disease burden in vulnerable patients, such as the elderly.…”
mentioning
confidence: 91%
“…Clostridium perfringens is an important pathogen known to cause disease in humans and animals (1, 2). Notably, the pathogenesis of C. perfringens -associated infections is largely attributed to the wide array of toxins this species can produce, with >20 toxins currently identified (3, 4). This Gram-positive spore former has been associated with foodborne and non-foodborne diarrhoeal diseases in humans, and preterm-necrotising enterocolitis (5, 6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation